2008
DOI: 10.1016/j.cell.2008.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Mre11 Dimers Coordinate DNA End Bridging and Nuclease Processing in Double-Strand-Break Repair

Abstract: SUMMARY Mre11 forms the core of the multifunctional Mre11-Rad50-Nbs1 (MRN) complex that detects DNA double-strand breaks (DSBs), activates the ATM checkpoint kinase, and initiates homologous recombination (HR) repair of DSBs. To de?ne the roles of Mre11 in both DNA bridging and nucleolytic processing during initiation of DSB repair, we combined small-angle X-ray scattering (SAXS) and crystal structures of Pyrococcus furiosus Mre11 dimers bound to DNA with mutational analyses of ?ssion yeast Mre11. The Mre11 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
609
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 438 publications
(643 citation statements)
references
References 43 publications
27
609
1
1
Order By: Relevance
“…Mre11, one of important DSB repair elements, is required for DNA-DSB repair including non-homologous end-joining repair system and homologous recombination repair system. Ding et al, 2006;Williams et al, 2007Williams et al, , 2008. It also can stabilize Rad50 and Nbs1 polypeptides and act as a chaperone for the MRN complex (Takemura et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Mre11, one of important DSB repair elements, is required for DNA-DSB repair including non-homologous end-joining repair system and homologous recombination repair system. Ding et al, 2006;Williams et al, 2007Williams et al, , 2008. It also can stabilize Rad50 and Nbs1 polypeptides and act as a chaperone for the MRN complex (Takemura et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies in yeast have shown that the dimerization function of the hook domain underlies the influence of this domain on DSB repair, telomere maintenance, and meiotic DSB formation (Wiltzius et al 2005). In cis, the globular domain could bridge two DNA ends in a manner that would promote NHEJ (Williams et al 2008). In this mode, end-to-end DNA bridging is effected by adjacent monomeric components of the dimeric globular domain (Lammens et al 2011;Lim et al 2011).…”
Section: ó 2014 Roset Et Al This Article Is Distributed Exclusivelymentioning
confidence: 99%
“…With respect its role in HDR, genetic and physical evidence suggests that the primary function of the Mre11 complex is to promote HDR between sister chromatids via the hook and coiled-coil domains of Rad50 (Bressan et al 1999;Hartsuiker et al 2001;Gonzalez-Barrera et al 2003;Wiltzius et al 2005;Hohl et al 2011). Mre11 complex-mediated NHEJ appears to be primarily dependent on DNA-binding sites in the globular domain (Williams et al 2008(Williams et al , 2009), although we showed that the hook and coiled-coil domains also influence this process, presumably via long-range effects on the disposition of globular domain components (Hohl et al 2011). …”
mentioning
confidence: 99%
“…The MRN complex tethers the DNA ends [10,11], leading to the recruitment and activation of the ATM kinase [12,13]. The MRN complex is also thought to participate in ATR-CHK1 kinase activation by facilitating DNA end resection [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…MRE11 is a conserved protein with an N-terminal nuclease domain [11,34] and a DNA-binding region [10,35] encompassing the GAR motif [36]. MRE11 nucleasedefective mice have been generated (Mre11 H129N/H129N ), defining a physiological role of the MRE11 nuclease activity in homologous recombination and the maintenance of genomic stability [30].…”
Section: Introductionmentioning
confidence: 99%